2011
DOI: 10.1136/bjsm.2010.081554.23
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness before and after moderate intensity exercise in athletes and controls: a cross-sectional observational study

Abstract: BackgroundArterial stiffness is an independent predictor for cardiovascular disease and mortality. There has been no previous research comparing the acute effects of exercise on arterial stiffness in resistance and endurance athletes. This information would help to reveal how arterial function responds to exercise training.ObjectivesTo measure and compare arterial stiffness and hemodynamic variables in resistance athletes, endurance athletes and controls, before and after moderate intensity exercise.MethodsCen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…This is best shown by the increasing publication rate, and also by the centre's increasing level of funded research activity. Work done by the students has helped build important collaborations within the university and also professional sport [14][15][16] . The Queen Mary University of London iBSc in Sports and Exercise Medicine has established itself during the past decade as a popular and well subscribed course for undergraduate medical students.…”
Section: Discussionmentioning
confidence: 99%
“…This is best shown by the increasing publication rate, and also by the centre's increasing level of funded research activity. Work done by the students has helped build important collaborations within the university and also professional sport [14][15][16] . The Queen Mary University of London iBSc in Sports and Exercise Medicine has established itself during the past decade as a popular and well subscribed course for undergraduate medical students.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of acute moderate exercise was evaluated by Dulai et al, who compared endurance-trained with resistance-trained subjects and sedentary controls at rest and after acute exercise. They found no differences in PWV values between the groups at rest, while after exercise, PWV and systolic blood pressures increased in endurance athletes, but not in controls and resistance-trained athletes (Dulai et al, 2011). Very young sportsmen, aged 11-16 years, were compared to sedentary controls at rest and after dynamic and isometric exercise.…”
Section: Effects Of Various Types Of Physical Training On Arterial Stiffnessmentioning
confidence: 97%
“…Some other studies reported no differences in aortic PWV between endurance athletes and healthy non-athlete controls (Dulai et al, 2011;Rátgéber et al, 2017). The effects of intense resistance training on arterial compliance were also evaluated, but the results were contradictory (Miyachi, 2013).…”
Section: Effects Of Various Types Of Physical Training On Arterial Stiffnessmentioning
confidence: 99%
“…• Ήπια αύξηση της κρεατινίνης πλάσματος: Ως προς την ένταση της άσκησης, τα μέχρι τώρα δεδομένα είναι ασαφή ως προς το εάν η χαμηλής ή μέτριας έντασης άσκηση επηρεάζει με ωφέλιμο τρόπο την ελαστικότητα των αγγείων. 256 Επίσης, φαίνεται και το είδος της άσκησης να έχει σημαντικό ρόλο: ενώ αναφέρθηκαν μελέτες που τεκμηριώνουν την ευνοϊκή επίδραση στην ελαστικότητα των αγγείων της άσκησης αντοχής, άλλες μελέτες δείχνουν ότι η άσκηση αντιστάσεων δεν ωφελεί 257 ή αντιθέτως, μπορεί να επιδράσει δυσμενώς στην αρτηριακή ελαστικότητα 258 Υπάρχουν πολύ περιορισμένα δεδομένα σχετικά με τους υποκείμενους μηχανισμούς μέσω των οποίων η τακτική άσκηση έχει ευεργετικές επιδράσεις στα αγγεία.…”
Section: ο ρόλος του εξωκυτταρικού υποστρώματοςunclassified